Degree of Approximation of Functions f~∈Hω Class by the (Np·E1) Means in the Hölder Metric - Vishnu Narayan Mishra; Kejal Khatri (International Journal of Mathematics and Mathematical Sciences)
A new estimate for the degree of approximation of a function f˜∈Hω class by (Np·E1) means of its Fourier series has been determined. Here, we extend the results of Singh and Mahajan (2008) which in turn generalize the result of Lal and Yadav (2001). Some corollaries have also been deduced from our main theorem.